Pengaruh kompensasi finansial dan motivasi mengajar terhadap kinerja Guru SMK Wahid Hasyim Glagah - Darianto Darianto; Siti Musarofah; Ayu Lestari (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study aims to examine and analyze the effect of financial compensation and teaching motivation on the performance of SK Wahid Hasyim Glagah teachers considering the importance of human resource potential in a school operating system. This research was conducted at the Wahid Hasyim Glagah vocational school, the sample used was 100% of the number of teachers and used quantitative methods. The data were obtained statistically with the SPSS for windows 26.0 program. The results of the study simultaneously financial compensation and teaching motivation had a positive and significant effect on the performance of SMK Wahid Hasyim Glagah teachers. Partially, financial compensation and teaching motivation have a significant effect on the teacher's performance at SMK Wahid Hasyim Glagah.